How do you solve #5/(y-2) = y+2#?
the expression now becomes:
By signing up, you agree to our Terms of Service and Privacy Policy
To solve the equation 5/(y-2) = y+2, you can start by multiplying both sides of the equation by (y-2) to eliminate the denominator. This gives you 5 = (y+2)(y-2). Expanding the right side of the equation, you get 5 = y^2 - 4. Rearranging the equation, you have y^2 - 4 - 5 = 0, which simplifies to y^2 - 9 = 0. Factoring the quadratic equation, you have (y-3)(y+3) = 0. Setting each factor equal to zero, you get y-3 = 0 or y+3 = 0. Solving for y, you find y = 3 or y = -3. Therefore, the solutions to the equation are y = 3 and y = -3.
By signing up, you agree to our Terms of Service and Privacy Policy
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
When evaluating a one-sided limit, you need to be careful when a quantity is approaching zero since its sign is different depending on which way it is approaching zero from. Let us look at some examples.
- 98% accuracy study help
- Covers math, physics, chemistry, biology, and more
- Step-by-step, in-depth guides
- Readily available 24/7